Integration of Ethnoscience in Deep Learning: Perception of Science Teacher Candidates - Agus Muliadi; Ika Nurani Dewi (Jurnal Penelitian Pendidikan IPA, 2022)
Study aims to explore the perceptions of science teacher candidates regarding the integration of ethnoscience in deep learning. This study is exploratory research conducted at the Mandalika University of Education with research subjects of 28 students. This research uses a research instrument in the form of a closed questionnaire with answers using a Likert scale and has been validated by experts. This research data was analyzed using quantitative descriptive statistics and inferential statistics with independent sample t-test and Anova test. The results of this research are (1) perception of science teacher candidates regarding the integration of ethnoscience in deep learning based on gender, namely male students have an average 3.189 in Tall category and women 3.053 in Tall category; (2) the perception of male science teacher candidates regarding the integration of ethnoscience in deep learning based on home region, namely students from Mataram have an average at 2.983 in Tall category, West Lombok at 3.140 in Tall category, Central Lombok at 3.200 in Tall category, East Lombok at 3.100 in Tall category, and North Lombok at 3.067 in Tall category; (3) no significant difference in the perceptions of male and female students regarding the integration of ethnoscience in deep learning, as evidenced by the significance value of 0.371 which is greater than 0.05 (>0.05); (4) no significant difference in perception of science teacher regarding the integration ethnoscience in deep learning based on region, as evidenced by the significance value of 0.903 which is greater than 0.05 (>0.05).